TINGKAT PENGETAHUAN SUAMI TENTANG PENDAMPINGAN IBU SELAMA PROSES PERSALINAN DI KLINIK PERA MEDAN TAHUN 2019 - Aprilita Br Sitepu (STIKes Santa Elisabeth Medan, 2019)
The husband is the person who plays an important role in assisting the mother during the birth process to provide support and motivation for the mother, so that labor can take place smoothly and reduce the occurrence of complications for both mother and fetus. Goals: The purpose of this study was to determine the level of husband's knowledge about maternal assistance during labor in Medan Pera Clinic for the period March-September 2019. Method: This study is descriptive in nature with a cross sectional study design of 30 respondents and uses a total population method that uses secondary data from the clinical labor registration book and primary data from questionnaires submitted to each respondent. Results: The results of the study were obtained based on the level of knowledge with the most lack of knowledge, namely 66.67%, followed by those with sufficient knowledge, namely 26.67%, and the least knowledgeable, namely 6.67%. Based on the demographics of respondents based on education most had high school educational background of 76.67%, based on the number of children who had the most 2-5 children as many as 63.33%, based on work, most worked as entrepreneurs, as many as 83.33%, based on the source of information most obtained information from the environment that is as much as 56.67%. Conclusion: Health workers are expected to motivate more husbands to be able to prepare themselves early in assisting mothers during the delivery process so that the husbands not only know but also carry out what is already known about childbirth companions.